KEPEMIMPINAN KEPALA SEKOLAH ( Studi Kasus di SMP Kolese Kanisius Jakarta ) - Yohanes Andhi Kurniawan (Universitas Negeri Jakarta, 2018)
The objective of this research was to understand and to get picture of organizational communication, decision making and reward that used by School Principal at Canisius College Junior High School Jakarta. The data were collected through participant observation using interview, observation, document study and recording. The data analysis and interpretation indicates that (1) the interpersonal communication system is a main communication system, social networking and electronic communication become the main support in developing the communication. The communication that occurs such as oral, written and nonverbal communication which is applied in Downward communication nor Upward communication, (2) Decision was taken as a programmed and nonprogrammed decisions. The programmed decisions is the main task of a school leader and the nonprogrammed decisions is the strategic policy that taken to achieving the goal of the school which refers to the schools vision and mission, (3) The awarding highly prioritized both the intrinsic reward and extrinsic reward so that the teachers, staff and students feel very appreciated. It will always provide the best work for the school.